Peningkatan Kompetensi Kewirausahaan Pada Masa Covid 19 Bagi Pengusaha Aisyiyah - Moch. Tholib; Mutamimah Mutamimah; Ida Zahara Adibah (Universitas Muhammadiyah Yogyakarta, 2021)
The covid-19 pandemic has reduced the business income of Aisyiyah’s businesswomen. The purpose of this community service was to improve entrepreneurial competence, especially business financial management and assistance in making Business Registration Numbers and Micro Small Business Permits for Aisyiyah’s businesswomen during the covid-19. The program aimed to improve the entrepreneurial competence of Aisyiyah entrepreneurs during the Covid-19 pandemic. Implementation method: a) An initial study of the potential and business problems experienced by Aisyiyah’s businesswomen and discussing the topics needed. b) Implementation of entrepreneurial competency training, financial management for women entrepreneurs Aisyiyah, as well as assistance in making Business Registration Numbers and Micro Small Business Permits, c) Monitoring and evaluation. The results showed that the level of entrepreneurial competence increases, especially business financial management for Aisyiyah’s businesswomen. b). They are skilled in making financial reports, so they know the financial condition, weaknesses and strengths of the financial sector. c). Having good financial reports makes it easier for Aisyiyah’s businesswomen to get loans for business development. After being assisted in making Business Registration Numbers and Micro Small Business Permits, like business licenses and legality for the businesses of Aisyiyah’s businesswomen, they are more confident and more motivated in developing their business. The competence increase was shown by the high posttest score of 96.86% and much higher than the pre-test score, which only reached 0.083%. The implication was that these results could become input for the Aisyiyah Entrepreneurial School in improving the competence of Aisyiyah businesswomen and being able to develop the economy.